An investigation of aspects hindering the implementation of blended learning in EFL classes case study : The second year LMD students of English - Ait Hocine ,Meriem; Oubelaid, Nabila; Belhadj , Abd El Krim (Faculty of Letters and Foreign Languages Department of English, 2017)
This research aims at shedding lights on the obstacles hindering the implementation of blended learning in EFL classes. The current research focuses on exploring and defining what a blended learning is and how useful it is in an EFL class. It also aims at describing a well-designed blended learning course, how it is applied and how effective it is in motivating the learners in the learning process to eject the main criteria a teacher should take into consideration, implicitly the non-consideration of the criteria in question can make the use of a blended learning sterile. In order to reach the aim of this research, the work has to discuss and analyze the students‟ attitudes towards learning a language through the use of technology and multimedia to know what barriers block them in their learning process. The second year LMD students of English have helped in achieving the goal of this research through their participation in the questionnaire. Participants showed tendency toward the use of different technological tools